2021
DOI: 10.1371/journal.pone.0254921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microRNA-210 on wound healing among the patients with diabetic foot ulcer

Abstract: Aim Diabetic foot ulcer (DFU) is a major concern in diabetes and its control requires in-depth molecular investigation. The present study aimed to screen the expression of microRNA-210 (miR-210) and its association in hypoxic pathway in DFU patients. Methods The study consists of 3 groups of circulation samples (50 in each group of: healthy volunteers, T2DM and T2DM with DFU) and 2 groups of tissue samples (10 in each group of: control and T2DM with DFU). Expression of miR-210 and hypoxia inducible factor-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Although previous studies have reported that miRNAs were valid in diabetic wound healing, only one is currently available in clinical trials. 29 Therefore, further research is needed to advance the therapeutic role of miRNAs in refractory healing in diabetic wounds. This study explored the above issues and found that miR-185-5p was closely related to DFU and that the level of miR-185-5p in STZ-induced type 1 diabetes rats was higher than that in normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported that miRNAs were valid in diabetic wound healing, only one is currently available in clinical trials. 29 Therefore, further research is needed to advance the therapeutic role of miRNAs in refractory healing in diabetic wounds. This study explored the above issues and found that miR-185-5p was closely related to DFU and that the level of miR-185-5p in STZ-induced type 1 diabetes rats was higher than that in normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…22 This factor migrates to the nucleus, where it stimulates transcription of angiogenic genes, such as vascular endothelial growth factor A (VEGF-A), fibroblast growth factor (FGF2), transforming growth factor beta (TGF-b1), platelet-derived growth factor (PDGF), forkhead box O1 (FOXO1), erythropoietin (EPO), and stromal cell derived factor 1 alpha (SDF-1a). [22][23][24] HIF-1a-induced VEGF-A is mainly secreted by macrophages, and it binds to specific receptors on endothelial cells' membrane (VEGFR2). 25 Simultaneously, it stimulates proliferation and migration of endothelial cells to form new vessels.…”
Section: Molecular Targets For Angiogenesismentioning
confidence: 99%
“…23 Because angiogenesis is an essential process in DFU healing and there are miRNAs associated with this process, there may be an opportunity here to investigate and develop therapies that target these miRNAs. 15,24 Endothelial cells were hypothesized to be stimulated during inflammatory stress, as in diabetes, to secrete miR-191 into the plasma, where they act on zona occludens-1, a protein expressed on endothelial cells of the injured area. By acting on zona occludens-1, they suppress angiogenesis, leading to a delay in the healing of chronic wounds in patients with diabetes.…”
Section: Molecular Targets For Angiogenesismentioning
confidence: 99%
“…Compared to that in diabetic subjects, miR‐210 expression is increased and hypoxia‐inducible factor 1‐alpha (HIF‐1α) expression is reduced in the ulcer tissue of diabetic foot patients. Further studies have shown that miR‐210 participates in the molecular response of diabetic foot tissue and alleviates hypoxia‐induced apoptosis by directly targeting HIF‐1α and inhibiting the activation of HIF‐1α downstream pathways, and miR‐210 is considered to be a potential biomarker for diagnosing diabetic foot in the future 34 . We summarized the apoptotic role of mirnas in the healing of diabetic foot ulcers in Table 2.…”
Section: Overview Of Apoptosismentioning
confidence: 99%